ABOUT DYNAMICS IN DIGITAL IMAGE - ZABADAL, Lubomir (Trends in education, 2013)
In the following text, we discuss digital dynamics. We understand dynamics as an influence of dynamising algorithms on the movement of a digitally coded painting brush. The use of dynamics in creation of static images is linked with the creator's idea of real processes and materials and due to that, it can help the penetration of individuality into the digitally coded image.
Keywords: digitally coded image; dynamics; animated brush; parametrical brush